Risks of investment projects: assessment and management (Путеводитель предпринимателя)
The current period of development of the real sector of the Russian economy is characterized by growth in investment activity of industrial enterprises, and in this connection, the importance of research aimed at developing science-based methods of analysis of investment projects intended to implement in the industry. At the same time, because investment decisions involve a high level of risk, an essential requirement for their development is the management of risk in the investment planning. This article examines the nature, methods of assessment and methods of management of investment risk.